2013
DOI: 10.1007/s12032-013-0642-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential clinical significance of ERβ ON promoter methylation in sporadic breast cancer

Abstract: The aim of the study was to assess how hypermethylation of the ON promoter of the estrogen receptor beta (ERβ) gene affects its expression (at the mRNA and protein level) and to correlate these with some clinical and histopathological parameters. A total of 131 samples of frozen breast cancer tissue was analyzed. A custom-designed, two-step PCR method was used to measure the methylation index of the ERβ gene ON promoter region. Quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR) was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The treatment of cells with 5-AZAC was associated with an increased expression of ERβ [67]. In our study, we observed a significant association between ERβ promoter ON methylation and nodal metastasis in invasive breast cancer [68].…”
Section: Epigenetic Regulation Of Erβsupporting
confidence: 62%
See 1 more Smart Citation
“…The treatment of cells with 5-AZAC was associated with an increased expression of ERβ [67]. In our study, we observed a significant association between ERβ promoter ON methylation and nodal metastasis in invasive breast cancer [68].…”
Section: Epigenetic Regulation Of Erβsupporting
confidence: 62%
“…There was also a significantly lower expression of mRNA in pre-cancerous tissue compared to tissue in a more progressive breast cancer state [154]. Some researchers and our group came to the conclusion that the hypermethylation of the ESR2 gene ON promoter was associated with more progressed disease [67,68]. Based on the previous studies, hypermethylation could be a potential additional diagnostic/therapeutic marker that could be targeted by demethylation agents.…”
Section: Erβ In Breast Cancer and Its Metastasesmentioning
confidence: 83%
“…According to Mirza et al, patients with concurrent hypermethylation of ERβ and retinoic acid receptor β2 (RARβ2) showed a significantly shorter median OS [47]. Interestingly, another study found that the methylation level of the ON promoter could be a more reliable parameter for prognosis in breast cancer than ERβ1 mRNA and/or protein levels [111]. Therefore, these findings may indicate the role of ERS2 methylation in breast cancer development and treatment.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Two promoters, promoter 0K and 0N, control the transcription of ER-β [ 130 ]. The lack of ERβ1, ERβ2 and ERβ4 transcription in some breast, ovarian and prostate cancer tissues and cell lines may be attributed to methylation of CpG sites in the promoter 0N [ 131 ]. In contrast, the 0K promoter is demethylated in malignant breast and ovarian cancer cells, as well as in normal breast and ovarian epithelial cells [ 132 , 133 ].…”
Section: Epigenetic Regulation Of Er Expressionmentioning
confidence: 99%